Partial-Oral Antibiotic Therapy for Bone and Joint Infections in People With Recent Injection Drug Use. (7th January 2023) - Yang, Wei-Teng; Dombrowski, Julia C; Glick, Sara N; Kim, H Nina; Beieler, Alison M; Lan, Kristine F; Dhanireddy, Shireesha
Abstract: Background: Limited outcome data exist regarding partial-oral antibiotic therapy, defined as oral antibiotics as part of a patient's treatment, for bone and joint infections (BJIs) in people who inject drugs (PWID). Methods: We conducted a retrospective study of all PWID reporting drug use within 3 months and BJIs requiring ≥6 weeks of antibiotics in an urban safety-net hospital between February 1, 2019, and February 1, 2021. Treatment outcomes were assessed by chart review. Rates of failure, defined as death, symptoms, or signs concerning for worsening or recurrent infections, were assessed 90 and 180 days after completion of antibiotics. Univariate logistic regression was used to explore the association between covariates and failure. Results: Of 705 patients with BJI, 88 (13%) were PWID. Eighty-six patients were included in the final cohort. Forty-four (51%) were homeless, 50 (58%) had spine infection, 68 (79%) had surgery, and 32 of 68 (47%) had postoperatively retained hardware. Twelve (14%) of 86 patients received exclusively intravenous (IV) antibiotics, and 74 (86%) received partial-oral antibiotics. Twelve (14%) of 86 patients had patient-directed discharge. In those who received partial-oral antibiotics, the failure rate was 20% at 90 days and 21% at 180 days after completion of intended treatment. Discharge to a medical respite and follow-up with infectious diseases (ID) or surgery were negatively associated with odds of failure. Conclusions: Partial-oral treatment of BJI in PWID was a common practice and often successful when paired with medical respite and follow-up with ID or surgery.